1994
DOI: 10.1111/j.1365-3083.1994.tb03389.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Inhibits Leishmania‐lnduced Cell Proliferation but not Production of Interleukin‐6 and Tumour Necrosis Factor Alpha

Abstract: The immune response of normal human peripheral blood mononuclear cells (PBMC) after stimulation with human immunodeficiency virus-1 (HIV-1) antigens plus Leishmania donovani promastigotes in vitro was investigated. HIV-1-antigen stimulation of PBMC did not induce the intracellular accumulation of interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-alpha), or interferon-gamma (IFN-gamma). However, cells stimulated with L. donovani antigens exhibited the production of IL-6 and TNF-alpha, but not IFN-gamma. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[77] A vicious circle is established whereby the protozoan parasite Leishmania induces a more robust HIV-1 production and the virus mediates a greater parasitic replication. Indeed, it has been shown that HIV-1 infection increases the risk of developing VL by 100 to 2,300 times in areas of endemicity, reduces the likelihood of a therapeutic response and greatly increases the probability of relapse.…”
Section: Hiv Immunologymentioning
confidence: 99%
See 2 more Smart Citations
“…[77] A vicious circle is established whereby the protozoan parasite Leishmania induces a more robust HIV-1 production and the virus mediates a greater parasitic replication. Indeed, it has been shown that HIV-1 infection increases the risk of developing VL by 100 to 2,300 times in areas of endemicity, reduces the likelihood of a therapeutic response and greatly increases the probability of relapse.…”
Section: Hiv Immunologymentioning
confidence: 99%
“…In individuals with nonfunctional T-lymphocytes, such as in HIV-infected patients, Leishmania infection becomes increasingly problematic. [77]…”
Section: Hiv Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that HIV-1 inhibits the proliferative response to L. donovani (269); this reduced cellular response might be because the known inductive signal for gamma interferon (IFN-␥) is lacking or could be due to the direct influence of anti-inflammatory Th2 cytokines. Wolday et al (272) confirmed that HIV-1 can modulate in vitro and ex vivo cytokine production in response to Leishmania; the addition of HIV-1 to cultures decreased IFN-␥, IL-12, and IL-18 production and increased IL-4 and IL-10 production in response to Leishmania by peripheral blood monocytic cells from healthy donors, while cells from HIV-1-infected and coinfected patients failed to secrete IFN-␥ in response to Leishmania.…”
Section: Pathogenesis Vl-hiv Coinfectionmentioning
confidence: 99%
“…Early after the appearance and report of the first cases of Leishmania-HIV coinfection, it was evident that the presence of both pathogens concomitantly in the same host cell (the macrophage) might have enhanced reciprocal effects that influence the expression and multiplication of either one or both pathogens (36,269). It is thought that the parasite infection found concurrently with HIV induces chronic immune activation, and therefore an increased HIV load and accelerated progression of AIDS (27), whereas immunological disturbances caused by HIV are particularly favorable for the uncontrolled multiplication of the parasite.…”
Section: Pathogenesis Vl-hiv Coinfectionmentioning
confidence: 99%